Analysis of condensation and secondary flows at three-way junctions using optical visualization techniques and computational fluid dynamics. (August 2021) - Galindo, J.; Navarro, R.; Tarí, D.; Moya, F.
Highlights: Novel flow rig to study mixing of humid streams, with free optical access at outlet. Experimental (PIV) and numerical (RANS) study of secondary flows at junction outlet. Original application of laser visualization to characterize condensation patterns. 3D CFD model predicts flow and condensation in agreement with the experiments. Development of tools and guidelines to design junctions to minimize condensation. Abstract: Three-way junctions are employed in almost all piping systems, whenever two streams need to be merged into one duct. In some applications, the mixing between streams plays an important role for determining the performance of downstream elements. The situation is particularly interesting for low pressure Exhaust Gas Recirculation (EGR) junctions featured in piston engines, where warm humid exhaust gases meet cold fresh air, since the mixing of both streams can produce water condensation. This condensation deteriorates the integrity and performance of the adjacent compressor wheel. This work explores the aforementioned flow configuration in a three-way junction by means of a novel gas test bench that allows the characterization of the transversal section at the junction outlet, and 3D Computer Fluid Dynamics (CFD) simulations embedded with a previously-developed condensation model. Two optical techniques are employed: laser particle image velocimetry, which is used to characterize the cross-section secondary flows, and planar laser-induced visualization, which is employed for the first time to obtain the condensation pattern. The experimental measurements are conducted at two different working points and for two different three-way junction designs, being in agreement with 3D CFD simulations. Particularly, the overall luminosity captured in the experiments presents the same trends than the numerical condensed mass fraction. This innovative validation proves that a CFD model employing a psychrometric-based condensation submodel can be used as a tool to quantify the condensation produced in a three-way junction. The proposed tools are shown to be helpful for the development of advanced LP-EGR systems to reduce N O X, C O 2 and particulate matter emissions during engine warm-ups.